Mechanical properties of 3D voxel-printed materials for cardiovascular tissue imitation - Illi, Joël; Bergamin, Manuel; Ilic, Marc; Stark, Anselm W.; Bracher, Stefan; Hofmann, Martin; Burger, Juergen; Shiri, Isaac; Haeberlin, Andreas; Gräni, Christoph (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundCardiovascular patient-specific phantoms can improve patient care through testing and simulation. However, materials like silicone and 3D-printing polymers differ mechanically from biological tissues. Agilus30 Clear, the primary material for 3D-printed phantoms, is much stiffer, nearly isotropic, and lacks strain-hardening behavior. To overcome these challenges, a novel 3D voxel-printing approach may provide an effective solution.Methods/aimThis study aimed to explore the applicability of 3D voxel printing, assess how different parameters (strand structure, density, and orientation) affect mechanical properties, and compare them to established phantom materials and porcine cardiovascular tissues. Progressive uniaxial cyclic tension tests were performed across nine stages, varying strain rates and target strain levels, with elastic modulus calculated for comparison. The goal was to stepwise assess whether the overall material stiffness can be reduced, achieving anisotropy and replicating strain-hardening behavior.ResultsIn the first step, varying the strand density, the tested samples showed a 0%–60% strain modulus of elasticity of 0.215–0.278 N/mm2, representing a 4–5-fold reduction in elastic modulus compared to that of the base material, Agilus30 Clear. In the second step, varying the orientation of the structures had a significant influence on the elastic modulus, which was measured. The 0%–60% modulus of elasticity decreased to 0.161–0.192 N/mm2, displaying anisotropic material behavior. In the third step, two strand structures specifically designed to mimic fiber recruitment were tested. These resulted in slightly flatter (more linear) stress–strain curves compared to the non-linear strain-softening behavior observed in Agilus30 Clear. However, they still fell short of replicating the desired non-linear strain-hardening behavior characteristic of fiber recruitment in cardiovascular tissues.ConclusionThe novel 3D voxel-printing material approach resulted in reduced elastic modulus, anisotropic behavior, and strain-hardening properties, providing a much closer representation of the mechanical behavior of porcine cardiovascular tissues compared to other available phantom materials. However, there is still significant potential for optimization through further exploration of fiber recruitment replication.